Developmental neurotoxicity of chlorpyrifos: delayed targeting of DNA synthesis after repeated administration - Dam, K; Seidler, F.J; Slotkin, T.A (Brain research. Developmental brain research, 1998)
Despite the fact that they recover more rapidly from cholinesterase inhibition than do adults, developing animals are more sensitive to delayed neurotoxicity caused by chlorpyrifos exposure. Previous studies indicate that acute, high dose chlorpyrifos exposure of developing rats interferes with synthesis of brain macromolecules, dependent upon a critical maturational stage and upon regional disparities in cholinergic innervation. In order to determine whether chronic, lower level chlorpyrifos exposure targets similar developmental events, rats were treated daily on postnatal days 1–4, using a dose (1 mg/kg, s.c.) that caused no mortality or weight deficits and that produces minimal cholinesterase inhibition. At the end of the treatment period, we examined macromolecule synthesis in three brain regions possessing disparate maturational profiles and cholinergic innervation: the brainstem, which undergoes its primary phase of neurogenesis prenatally and develops prominent cholinergic innervation, the forebrain, which develops somewhat later but also becomes cholinergically enriched, and the cerebellum, which undergoes neurogenesis postnatally and remains poor in cholinergic innervation. Four h after the last chlorpyrifos treatment, no effects were seen for DNA, RNA or protein synthesis. However, on postnatal day 5 (24 h after the last treatment), robust deficits in DNA synthesis were observed in brainstem and forebrain, with lesser effects on the cerebellum. Although the brain regional selectivity is compatible either with differences in critical maturational phases or with targeting of cholinergically-enriched brain regions, we found no significant effects in the heart, despite the fact that it is also receives cholinergic innervation. Effects on DNA synthesis were not evident 4 h after the last dose, but then appeared after 24 h. As the 4-h point is 28 h after the third dose, this suggests that a cumulative threshold needs to be exceeded in order for the delayed neurotoxicity to appear. At the point at which DNA synthesis was inhibited in brainstem and forebrain, no effects were seen for RNA or protein synthesis, indicating selectivity for macromolecule synthesis associated with cell replication. These data indicate that otherwise subtoxic, chronic exposures to chlorpyrifos nevertheless target DNA synthesis, and by inference, cell replication, in selective brain cell populations, early events that are likely contributors to the deficits in cell number that appear several days later.